Peripartum hysterectomy at a tertiary center - Gurung, Monica; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To find out the incidence, indications, complication of emergency peripartum hysterectomy in a tertiary care center. Methods: This was a retrospective study conducted over a period of 18 months from April 2017 to October 2018 at Paropakar Maternity and Women’s Hospital in Kathmandu. Data were obtained from the operation theater register and record section. Results: Out of 30917 deliveries in 18 months 18 had lifesaving emergency peripartum hysterectomy (0.58 per 1000 deliveries). The most common indication being morbidly adherent placenta/placenta previa (8; 44%) followed by ruptured uterus (5; 28%), uterine atony (4; 22%). The most common risk factor is attributed to previous cesarean section (11; 61%) followed by abnormal placentation (7; 39%). Most common morbidity was febrile morbidity followed by wound infection and bladder injury. Conclusion: Abnormal placentation and past cesarean section contributed to be the major indication of peripartum hysterectomy.